Nikolay Petrovich Demichev - Astrakhan State Medical Academy, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article deals with the 80th birthday of a member of the International Academy of Science, Doctor of Medical Science, professor of the Department of Traumatology, Orhtopaedics and Field Surgery of Astrakhan State Medical Academy (Russia), Honoured Doctor of the Russian Federation, member of the Union of Journalists of Russia, member of the Union of Writers of Russia, Honourary Freeman of Astrakhan Demichev Nikolay Petrovich.